1999
DOI: 10.1046/j.1365-2885.1999.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma pharmacokinetics and bioavailability of ceftiofur sodium and ceftiofur hydrochloride in pigs after a single intramuscular injection

Abstract: Ceftiofur sodium, a broad-spectrum cephalosporin, is active against gram-positive and gram-negative pathogens of veterinary importance. Two studies were designed to compare the intramuscular bioavailability of the current sodium salt and the new hydrochloride salt in pigs at doses of either 3 mg or 5 mg ceftiofur equivalents (CE)/kg body weight. Twenty-six healthy young pigs were selected for these two-period, two-treatment crossover studies, 12 for the 3 mg/kg study and 14 for the 5 mg/kg study. Each animal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 6 publications
2
31
4
1
Order By: Relevance
“…The C max of DCA obtained in the group treated with ceftiofur–PHBV was 1.9 times lower than the C max (11.8±1.6 μg/mL) described in the study of Brown et al in pigs that received 3 mg/kg weight via im injection 18. Also, the C max of DCA in the group of ceftiofur–PHBV was 1.6 times lower than the C max (10.3±1.2 μg/mL) reported by Goudah in camels treated with 2.2 mg/kg weight of ceftiofur using the same route of administration 31.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…The C max of DCA obtained in the group treated with ceftiofur–PHBV was 1.9 times lower than the C max (11.8±1.6 μg/mL) described in the study of Brown et al in pigs that received 3 mg/kg weight via im injection 18. Also, the C max of DCA in the group of ceftiofur–PHBV was 1.6 times lower than the C max (10.3±1.2 μg/mL) reported by Goudah in camels treated with 2.2 mg/kg weight of ceftiofur using the same route of administration 31.…”
Section: Resultscontrasting
confidence: 65%
“…For the elimination half-life (t ½ ), ceftiofur–PHBV showed a longer plasma circulation time than nonencapsulated ceftiofur, and also longer t ½ than others studies in pigs (16.7±2.3 hours) injected with 3 mg/kg weight (im) of ceftiofur, llamas (8.1±1.7 hours) injected with 2.2 mg/kg (im), and alpacas (8.2±1.3 hours) that received doses in the range of 1.30 to 1.51 mg/kg via im injection 18,32. In addition, the sustained release of ceftiofur from ceftiofur–PHBV was longer (17 days) than that of other long-acting drug delivery systems based on liposomes (2 days) and crystalline-free acid sterile suspension (10 days) 33,34.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, the pharmacokinetic data for both the SC and IM administration illustrate that the availability of the sodium salt of ceftiofur from an aqueous solution is similar to that of the HCl salt from an oil suspension in cattle (Table 8.3 , with the exception of the higher blood plasma maximum concentration for the solution [ 36 ] ). Similar fi ndings of therapeutic equivalence were noted in swine [ 37 ] . This further illustrates the complex interplay of factors at the site of injection including the solubility and the rate of dissolution.…”
Section: Prodrugssupporting
confidence: 79%
“…In the Amazon parrots, ceftiofur was declined to 0.27 µg/g in the plasma by 24 hr post intramuscular administration at the concentration of 10 mg/kg body weight. Brown et al [3] carried out a comparative study of plasma pharmacokinetics of ceftiofur sodium and ceftiofur hydrochloride in pigs after a single intramuscular injection at the dose of 3 mg or 5 mg/body weight, and analyzed these in the plasma with HPLC method. The analytical results showed that the concentration of ceftiofur sodium at 72 hr after the 3 mg injection was 0.27 µg/g, and that at 96 hr after the 5 mg injection was 0.224 µg/g.…”
mentioning
confidence: 99%